Research on optimal control method of hybrid electric vehicles. (September 2013) - Lian, Jing; Han, Hu; Li, Linhui; Zhou, Yafu; Feng, Jian
Energy saving and environmental protection are the two main themes of today's auto industry development. The hybrid electric vehicle (HEV) has become one of the most practical significant ways to solve energy and emission problems with good fuel economy and lower emissions. Aimed at the present HEV control methods, which have problems such as power loss, low efficiency of the system, the deterioration of the lubrication conditions, and so on, from the points of view of the overall efficiency of drive system, an optimal control method for a HEV is proposed to solve these problems. Firstly, all the possible operating modes are formulated. Then the efficiency evaluation equations of different modes are constructed. Next, according to the battery state of charge, this method determines the possible operating modes, and then the efficiency of different modes is calculated by means of the demand torque. Comparing the efficiency of different modes, the mode with the highest efficiency is obtained so that the engine torque and motor torque are distributed to enable the engine and motor output to correspond with this torque. Finally, the proposed method is simulated; the results show that it reduces system power loss and vehicle fuel consumption and emissions, and that it also protects the life of the transmission parts and lubrication conditions to some extent, achieving significant improvements.